Herd Immunity to Hepatitis B in the Russian Federation in 2017–2019 - S. N. Kuzin; T. A. Semenenko; V. V. Klushkina; N. V. Vlasenko; N. S. Churilova; Ya. V. Panasyuk; E. N. Kudryavtseva; M. I. Korabel'nikova; D. V. Dubodelov; Z. S. Rodionova; G. G. Solopova; M. V. Konopliova; et al. (Эпидемиология и вакцинопрофилактика, 2022)
Relevance. Hepatitis B is a global problem of global and Russian public health due to its high prevalence and the possibility of forming a chronic form of the disease with the development of cirrhosis and hepatocellular carcinoma.  Aims. Assessment of the herd immunity to hepatitis B in the population of the Russian Federation in 2017‒2019.Materials and methods. The research was carried out at the Central Institute of Epidemiology within the framework of a large-scale program to assess herd immunity to hepatitis B in the population of the Russian Federation. The results of studies for the presence of anti-HBs in various subjects of the Russian Federation in 2017 to 2019, which were performed in accordance with MU 3.1.2943-11, were analyzed. Additionally, as a reference study in 2020, a survey of donors in Moscow (n = 427) was conducted for the presence of anti-HBs. Standard methods of descriptive statistics Microsoft Excel and STATISTICA 12.0 (StatSoft, USA) were used for statistical processing. The mean values were estimated taking into account the 95% confidence interval [95% CI] (according to the Klopper-Pearson method (exact method).Results. The average annual values of the proportion of persons with protective immunity against hepatitis B for 2017, 2018 and 2019 were 70.03%, 67.95% and 66.36%, respectively. Significant differences were revealed in the average values of the proportion of persons with a protective level of anti-HBs in the Federal Districts (FD): higher than the average Russian indicators were found in the Northwestern (74.2%), Southern (71.0%) and Far Eastern FD (70.7%). In 44 subjects of the Russian Federation during the observation period, the proportion of persons with protective immunity against hepatitis B was less than 60%.Conclusion. The necessity of optimizing the system of serological monitoring of post-vaccination immunity against hepatitis B is substantiated, which will increase the effectiveness of preventive measures nationwide